Binomial schedule for an M/G/1 queueing system with an unreliable server. (1st January 2013) - Ba-Rukab, Omar M.; Tadj, Lotfi; Ke, Jau-Chuan
We consider in this paper a queueing system where, at a service completion epoch, the server decides to serve the next customer or take a vacation, to perform some auxiliary work. If a vacation is taken, the server again has to decide, at the end of the vacation, whether to take another one. This process continues for a maximum of K vacations. We call this a binomial schedule. We further assume that the server is unreliable and may break down anytime while providing service. Analysis of this system yields to the explicit expression of the optimal number of vacations K * . Numerical illustrations are provided.